Q. 205.0( 1 Vote )

# If y =(tan^{–1}x)^{2}, show that

Answer :

Given: y =(tan^{–1}x)^{2}

To show:

given y =(tan^{–1}x)^{2}

Now applying first derivative with respect to x, we get

Now applying the power rule of differentiation, we get

And we know differentiation of , substituting this in above equation, we get

Now applying second derivative with respect to x, we get

Taking out the constant term, we get

Now applying the quotient rule of differentiation, we get

And we know differentiation of , substituting this in above equation, we get

Now applying the sum rule of differentiation, we get

Now we will consider the LHS,

Now we will substitute the values from equation (i) and (ii)in above equation, we get

⇒=(2[1-2x(tan^{-1}x)])+2x(2(tan^{-1}x))

⇒=(2[1-2x(tan^{-1}x)]+ 2x(tan^{-1}x))

⇒=2=RHS

Hence proved

Rate this question :

If y = tan^{-1}x, find in terms of y alone.

If y = sin^{-1} x, show that

If y = 3 cos(log x) + 4 sin(log x), show that

Mathematics - Board Papers

If x = t^{2}, y = t^{3}, then is

If x = a cos θ + b sin θ, y = a sin θ – b cos θ, show that

Mathematics - Board PapersIf prove that

Mathematics - Exemplar

If y =(tan^{–1}x)^{2}, show that

If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}